Correlation between static postural balance, falls and pick torque isokinetic of extensors and flexors of the knee in elderly - Stocco, Marieli Ramos; Pires-Oliveira, Deise Aparecida de Almeida; Oliveira, Laís Campus de; Oliveira, Raphael Gonçalves de; Martini, Fábio Antônio Néia; Oliveira-Silva, Iransé; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Declines of static postural balance and muscle strength, especially of lower limbs are strong predictors of falls in the elderly. Objective: The objective of this study was to identify the possible correlation between static postural balance, falls and isokinetic torque peak of knee extensors and flexors in the elderly. Methods: A cross-sectional study with anthropometric evaluation of static postural balance in unipodal limb support was performed using the force platform, flexural strength test and knee extension of the dominant limb using the isokinetic dynamometer and the application of a structured questionnaire on falls. They agreed to participate in the study 106 volunteers of both sexes through the signing of the free and informed consent. The data were treated in the Statistical Package for the Social Sciences program version 20.0. Results: There was a weak positive correlation between center of pressure (COP) area and peak flexion torque (r=0.204, p=0.041) and extension (r=0.228; p=0.022) of the knee, as well as peak extension (r=0.319, p=0.001) and lateral mean (r=0.324, p=0.001). A moderate positive correlation between COP area and anteroposterior velocity (r=0.694, p=0.000) and lateral mean (r = 0.646; p = 0.000) and strong positive correlation was found only between peak flexion torque and knee extension (r=0.719, p=0.000). Conclusion: There was a weak correlation between static postural balance and dominant lower limb muscle strength, and there was no correlation between falls and lower limb muscle strength, or between falls and static postural balance in the studied sample.